ANALYSIS OF ROOM RENTAL CALCULATIONS TO INCREASE INCOME IN MAKASSAR HAJJ GENERAL HOSPITAL - Muttalib, Abdul; Syamsiah, Syamsiah; Fitrianti, Fitrianti (Perpustakaan dan Penerbitan Unismuh Makassar, 2018)
This study aims to compare or calculate the calculation of room rent at Makassar Hajj hospital. The object of this research is Makassar haju hospital located in Makassar city. In this writing the author uses quantitative writing methods. The results of the data analysis are done by processing primary data that is about all hospital operating costs incurred in the previous period, then the data is processed. The results showed that the effect of inpatient income on the income level of Makassar Hajj Hospital. In 2011 the level of inpatient admission was Rp. 1,988,230,000 to hospital revenue. In 2012, the level of inpatient income rose to Rp. 2,174,640,000, - to hospital revenue. In 2013, there was also an increase in hospital revenue due to inpatient revenues increasing by Rp. 2,077,880,000, - And in 2014, inpatient revenue also increased to hospital revenue by Rp.2,123,630,000.- From the results obtained above, it shows that the increase in revenue from Makassar Hajj Hospital was influenced by inpatient revenue. Thus, the proposed hypothesis is accepted.